Hydrological Response and Complex Impact Pathways of the 2015/2016 El Niño in Eastern and Southern Africa. Issue 1 (5th January 2018) - Siderius, C.; Gannon, K. E.; Ndiyoi, M.; Opere, A.; Batisani, N.; Olago, D.; Pardoe, J.; Conway, D.
Abstract: The 2015/2016 El Niño has been classified as one of the three most severe on record. El Niño teleconnections are commonly associated with droughts in southern Africa and high precipitation in eastern Africa. Despite their relatively frequent occurrence, evidence for their hydrological effects and impacts beyond agriculture is limited. We examine the hydrological response and impact pathways of the 2015/2016 El Niño in eastern and southern Africa, focusing on Botswana, Kenya, and Zambia. We use in situ and remotely sensed time series of precipitation, river flow, and lake levels complemented by qualitative insights from interviews with key organizations in each country about awareness, impacts, and responses. Our results show that drought conditions prevailed in large parts of southern Africa, reducing runoff and contributing to unusually low lake levels in Botswana and Zambia. Key informants characterized this El Niño through record high temperatures and water supply disruption in Botswana and through hydroelectric load shedding in Zambia. Warnings of flood risk in Kenya were pronounced, but the El Niño teleconnection did not materialize as expected in 2015/2016. Extreme precipitation was limited and caused localized impacts. The hydrological impacts in southern Africa were severe and complex, strongly exacerbated by dry antecedent conditions, recent changes in exposure and sensitivity and management decisions. Improved understanding of hydrological responses and the complexity of differing impact pathways can support design of more adaptive, region‐specific management strategies. Plain Language Summary: The 2015/2016 El Niño was one of the three most severe on record. El Niño is commonly linked to droughts in southern Africa and extreme rainfall in eastern Africa but no two El Niño's are the same. We present an analysis of the impact of the 2015/2016 El Niño in eastern and southern Africa, focusing on Botswana, Kenya, and Zambia. We use field measurements and observations from satellites of rainfall, river flow, and lake levels in combination with insights from experts in each country about awareness, impacts, and responses. Our results show that drought conditions prevailed in large parts of southern Africa, reducing river runoff and contributing to unusually low lake levels in Botswana and Zambia. This led to water supply disruption in Botswana and hydroelectric load shedding in Zambia. Warnings of flood risk in Kenya were pronounced, but the El Niño did not materialize as expected in 2015/2016. Extreme rainfall was limited and caused only localized impacts. Improved understanding of the regional impact of El Niño will help to be better prepared for the next El Niño. Key Points: Quantitative and qualitative data provide insights into hydrological impact pathways of precipitation anomalies associated with the El Niño of 2015/2016 Variable teleconnection patterns, antecedent hydrological conditions and changing socioeconomic boundary conditions led to complex impact pathways of this El Niño event Our findings show the need for diverse management responses, with adaptive reservoir management required and diversification of energy and water sources essential